The Law of the Outlaw: Law and Order With, Within, and Beyond Criminal Groups - Lamotte, Martin; Rodgers, Dennis (Swiss Journal of Sociocultural Anthropology, 2024)
This article introduces the special issue through a review of Francophone and Anglo-Saxon legal anthropology traditions, before situating the law of the outlaw within these and outlining its potential contribution towards the development of a pragmatic approach to law.